6(2x-6)=6(4-x)

Simple and best practice solution for 6(2x-6)=6(4-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2x-6)=6(4-x) equation:


Simplifying
6(2x + -6) = 6(4 + -1x)

Reorder the terms:
6(-6 + 2x) = 6(4 + -1x)
(-6 * 6 + 2x * 6) = 6(4 + -1x)
(-36 + 12x) = 6(4 + -1x)
-36 + 12x = (4 * 6 + -1x * 6)
-36 + 12x = (24 + -6x)

Solving
-36 + 12x = 24 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-36 + 12x + 6x = 24 + -6x + 6x

Combine like terms: 12x + 6x = 18x
-36 + 18x = 24 + -6x + 6x

Combine like terms: -6x + 6x = 0
-36 + 18x = 24 + 0
-36 + 18x = 24

Add '36' to each side of the equation.
-36 + 36 + 18x = 24 + 36

Combine like terms: -36 + 36 = 0
0 + 18x = 24 + 36
18x = 24 + 36

Combine like terms: 24 + 36 = 60
18x = 60

Divide each side by '18'.
x = 3.333333333

Simplifying
x = 3.333333333

See similar equations:

| p+15=0 | | 1/6/1/2 | | 5.6*10= | | -8-k=-12 | | -3-m=9 | | x^2+15x=-54 | | -20+k=-31 | | 17-5+x=5+9-1 | | 1/4(10x-5)=4 | | -16+b=-13 | | Log(x+1)+log(x-1)=log(x+1) | | 9+m=12 | | 22/25.15/52.8/33 | | y=-1(2)-2 | | y=-1(1)-2 | | y+(2)=-6 | | y+(-6)=-6 | | x-7.3=-5.7 | | 7+24/2*5-9= | | 2(5)+y=10 | | 13x-35=5x+1 | | 2(2)+y=10 | | 16+(-20)= | | y=2(9)-9 | | x^2=-640 | | 4(3x+5)-8x=14+16x | | y=2(2)-9 | | y=2(-4)-9 | | 2y+2(-6)=16 | | -8=-2/w | | 2y+2(-7)=16 | | -1.7x=-850 |

Equations solver categories